Preservice Science Teachers’ Opinions on E-Exams - Ozkan Yilmaz (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
With the developing information technologies in the new century, changes are experienced in every area of life and its reflections are seen in different areas. One of its reflections in the field of education is the E-exams, which have been used as an alternative to paper-pencil exams for years. Academic studies are needed for the integration of e-exams in the field of education and training. Thus, this new technology can be used efficiently in the field of education. Students' views, which are at the center of education and training, are of special importance for the proper use of the e-exam. In this study, how the student views on E-exam applications in science education is examined. The study was carried out with students studying science at higher education level. As a data collection tool, a prepared questionnaire form was used. As a result of the findings obtained, it was revealed that student views towards E-exam in science education were significantly positive and that E-exam instead of K-exam was positively welcomed by the student.